Photocurable adhesive, and bonding method

By adding non-ionic photo-based generators and organic peroxides to the photocuring glue, delaying curing by redox reactions, the existing photocuring glue has been solved, and the effects of medium delayed curing and long shelf life have been achieved.

JP2025040972APending Publication Date: 2025-03-25SEKISUI CHEMICAL CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024157655
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-12
Filing Date
2024-09-11
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The bonding strength of existing photocuring glues depends on ultraviolet light exposure, at least one bond needs to be transparent, limiting the application range. At the same time, the photocuring glue is completely cured after the initial ultraviolet light irradiation, making it difficult to delay the adhesion of the bonded body, and it is difficult to cure after the light stops, resulting in insufficient bonding strength.

Method used

The photocuring glue containing a radically polymerizable functional group is used, and a non-ionic photo-based generator and organic peroxide are added. The curing process of the colloid is controlled through the delayed redox reaction after light irradiation, so that it maintains a long service life within a certain period of time.

Benefits of technology

The medium delayed curing and long shelf life of photocuring glue are achieved, and the adhesion of the bonded body can be delayed in the absence of complete curing, ensuring full play to the bonding strength, and suitable for bonded bodies that are difficult to be transparent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025040972000008
    Figure 2025040972000008
  • Figure 2025040972000001
    Figure 2025040972000001
  • Figure 2025040972000002
    Figure 2025040972000002
Patent Text Reader

Abstract

To provide a photocurable adhesive having appropriate sustained curability, and a long pot life.SOLUTION: A photocurable adhesive includes: a compound having a radical-polymerizable functional group; a nonionic photo base generating agent; and an organic peroxide, where, when coating one calcium fluoride plate with the photocurable adhesive so as to become an area of 1 cm×1 cm and a thickness of 10 μm, irradiating the photocurable adhesive coated on the calcium fluoride plate, from its upper plane side, using an LED lump having a center wave length of 365 nm under a nitrogen atmosphere with a light intensity of 100 mW / cm2 for 30 sec., and thereafter, sandwiching the photocurable adhesive with the addition of the other calcium fluoride plate, the conversion ratio of the radical-polymerizable functional group right after the light irradiation is 20% or less, and the conversion ratio of the radical-polymerizable functional group when left standing at 25°C for one hour after the light irradiation is 80% or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a light-curing adhesive and a bonding method using the light-curing adhesive. [Background technology]

[0002] It is known that photocurable adhesives exert their adhesive strength when sandwiched between adherends made of the same material or different materials and irradiated with light such as ultraviolet light. For example, an adhesive containing a compound having a radically polymerizable functional group is known as a photocurable adhesive (for example, Patent Document 1). It is known that such photocurable adhesives exert their adhesive strength when a resin composed of a compound having a radically polymerizable functional group is cured by irradiating it with light such as ultraviolet light. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2023-11929 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, in photocurable adhesives, which exert their adhesive power by irradiating ultraviolet light when sandwiched between adherends, at least one of the adherends must be transparent to ultraviolet light, which limits the range of application.

[0005] As a solution to this problem, a method of irradiating a photocurable adhesive with ultraviolet light before bonding the adherends together is considered, but photocurable adhesives using compounds with radically polymerizable functional groups tend to completely cure the moment they are irradiated with ultraviolet light, making it difficult to bond the adherends together later. Alternatively, even if adhesion is attempted under conditions in which the photocurable adhesive is not completely cured by the initial irradiation with ultraviolet light, there is a problem that the curing does not progress easily after the light irradiation is stopped, making it difficult to obtain sufficient adhesive strength. In light of this background, there is a demand for photocurable adhesives that have an appropriate delayed curing property and a long pot life.

[0006] An object of the present invention is to provide a light-curing adhesive having an appropriate delayed curing property and a long pot life, and a bonding method using the light-curing adhesive. [Means for solving the problem]

[0007] The present specification discloses the following light-curing adhesive and bonding method.

[0008] Item 1. A photocurable adhesive comprising a compound having a radical polymerizable functional group, a nonionic photobase generator, and an organic peroxide, the photocurable adhesive being applied to one calcium fluoride plate in an area of ​​1 cm × 1 cm and a thickness of 10 μm, and then irradiating the upper surface of the photocurable adhesive applied to the calcium fluoride plate with a light intensity of 100 mW / cm using an LED lamp having a central wavelength of 365 nm under a nitrogen atmosphere. 2 and then sandwiched between two calcium fluoride plates, the photocurable adhesive has a conversion rate of 20% or less of the radical polymerizable functional group immediately after the light irradiation and a conversion rate of 80% or more when allowed to stand at 25°C for 1 hour after the light irradiation.

[0009] Item 2. A photocurable adhesive comprising a compound having a radical polymerizable functional group, a nonionic photobase generator, and an organic peroxide, wherein the content of the compound having the radical polymerizable functional group in the photocurable adhesive is 80% by weight or more, based on 100% by weight of the total amount of the photocurable adhesive, the compound having the radical polymerizable functional group comprises a compound having an ether bond, and the content of the compound having the ether bond in the photocurable adhesive is 20% by weight or more, based on 100% by weight of the compound having the radical polymerizable functional group, the nonionic photobase generator is a compound represented by the following formula (1), and the content of the nonionic photobase generator in the photocurable adhesive is 0.1% by weight or more and 0.5% by weight or less, based on 100% by weight of the compound having the radical polymerizable functional group.

[0010] [ka]

[0011] Item 3. The photocurable adhesive according to item 1, wherein the compound having a radically polymerizable functional group has an ether bond.

[0012] Item 4. The photocurable adhesive according to item 1 or 2, wherein the compound having a radically polymerizable functional group has a plurality of radically polymerizable functional groups.

[0013] Item 5. The photocurable adhesive according to any one of Items 1, 3, and 4, wherein the nonionic photobase generator is a compound represented by the following formula (1):

[0014] [ka]

[0015] Item 6. The photocurable adhesive according to any one of Items 1 to 5, wherein the organic peroxide has a percarboxylic acid structure.

[0016] Item 7. The photocurable adhesive according to any one of Items 1 to 6, further comprising a silane coupling agent.

[0017] Item 8. The photocurable adhesive according to item 7, wherein the content of the silane coupling agent in the photocurable adhesive is 0.1% by weight or more and 10% by weight or less, based on 100% by weight of the compound having a radical polymerizable functional group.

[0018] Item 9. The photocurable adhesive according to any one of items 1 to 8, further comprising a filler.

[0019] Item 10. The photocurable adhesive according to any one of Items 1 to 9, wherein the content of the solvent in the photocurable adhesive is 10% by weight or less relative to 100% by weight of the compound having a radical polymerizable functional group.

[0020] Item 11. A method for bonding adherends together using the photocurable adhesive according to any one of items 1 to 10, comprising the steps of applying the photocurable adhesive to one adherend and irradiating the photocurable adhesive with ultraviolet light, and attaching the other adherend to the photocurable adhesive within 10 minutes after the irradiation with ultraviolet light.

[0021] Item 12. The bonding method according to item 11, wherein a primer layer is applied in advance to at least one of the one adherend and the other adherend. Effect of the Invention

[0022] According to the present invention, it is possible to provide a light-curing adhesive having an appropriate delayed curing property and a long pot life, and a bonding method using the light-curing adhesive. [Brief description of the drawings]

[0023] [Figure 1] 1(a) to (c) are diagrams illustrating an example of a bonding method using the photocurable adhesive of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] The present invention will be described in detail below.

[0025] [Light-curing adhesive] The photocurable adhesive of the present invention contains a compound having a radically polymerizable functional group, a non-ionic photobase generator, and an organic peroxide.

[0026] In the first invention of the present application, a photocurable adhesive is applied to one calcium fluoride plate so as to have an area of ​​1 cm × 1 cm and a thickness of 10 μm, and in a nitrogen atmosphere, an LED lamp with a central wavelength of 365 nm is used to irradiate the photocurable adhesive from above the calcium fluoride plate at a light intensity of 100 mW / cm. 2 When the sample is irradiated with light at 25°C for 30 seconds and then sandwiched between the other calcium fluoride plate, the conversion rate of the radical polymerizable functional group immediately after the light irradiation is 20% or less, and when the sample is allowed to stand at 25°C for 1 hour after the light irradiation, the conversion rate of the radical polymerizable functional group is 80% or more.

[0027] In measuring the conversion rate, the photocurable adhesive is applied to one of the calcium fluoride plates so that the area is 1 cm × 1 cm and the thickness is 10 μm. In addition, when irradiating the upper surface of the photocurable adhesive with light, an LED lamp with a central wavelength of 365 nm is used with a light intensity of 100 mW / cm. 2 The plate is then exposed to light for 30 seconds. The photocurable adhesive is then sandwiched between the other calcium fluoride plate.

[0028] The conversion rate of the radical polymerizable functional group can be determined by measuring the FT-IR spectrum immediately after the light irradiation of the photocurable adhesive and after leaving it at rest at 25°C for 1 hour after the light irradiation. The conversion rate of the radical polymerizable functional group can be determined by the intensity of the reference peak in the FT-IR spectrum and the 1600 cm -1 ~1680cm -1 It can be calculated from the change in peak intensity before and after light irradiation in the vicinity using the following formula (2).

[0029] Conversion rate (%) = (1 - peak intensity ratio after irradiation / peak intensity ratio before irradiation) × 100 ... Equation (2) Peak intensity ratio before irradiation = (C = C peak intensity before light irradiation / reference peak intensity before light irradiation) Peak intensity ratio after irradiation = (C = C peak intensity after light irradiation / reference peak intensity after light irradiation)

[0030] The peak before light irradiation refers to a peak measured before the light-curable adhesive is irradiated with light, and the peak after light irradiation refers to a peak measured immediately after the light-curable adhesive is irradiated with light or after leaving the adhesive at rest at 25°C for 1 hour after light irradiation.

[0031] The reference peak refers to a peak attributable to a functional group or bond that does not change before and after irradiation with light having a central wavelength of 365 nm. Examples of the reference peak include a peak attributable to an ester group, a peak attributable to (CN) of an amide group, or a peak attributable to a cyclic ether (COC).

[0032] The light-curing adhesive of the first invention has the above-mentioned configuration, and therefore has an appropriate delayed curing property and a long pot life.

[0033] Conventionally, photocurable adhesives exert their adhesive force by, for example, irradiating ultraviolet light when sandwiched between adherends. However, when using such photocurable adhesives to bond adherends together, at least one of the adherends needs to be made of a material that transmits ultraviolet light, which limits the range of application of the adhesive.

[0034] One possible solution to this problem is to irradiate the photocurable adhesive with ultraviolet light before bonding the adherends together, but photocurable adhesives using compounds with radically polymerizable functional groups tend to completely cure the instant they are irradiated with ultraviolet light, making it difficult to bond the adherends together later.Alternatively, even if bonding is attempted under conditions where the photocurable adhesive is not completely cured by the initial irradiation with ultraviolet light, the curing does not progress easily after the light irradiation is stopped, making it difficult to obtain sufficient adhesive strength.

[0035] In response to this, the present inventors have found that it is possible to delay the curing of a resin formed from a compound having a radically polymerizable functional group by utilizing an oxidation-reduction reaction between an organic peroxide and a long-lived base generated from a non-ionic photobase generator.

[0036] In particular, in the photocurable adhesive of the first invention, in the above-mentioned conversion rate measurement, the conversion rate of the radical polymerizable functional group immediately after light irradiation is 20% or less, and the conversion rate of the radical polymerizable functional group when left to stand for 1 hour at 25° C. after light irradiation is 80% or more. Therefore, the photocurable adhesive of the first invention can appropriately delay the curing by light irradiation of a resin composed of a compound having a radical polymerizable functional group (has an appropriate delayed curing property).

[0037] In the second invention of the present application, the content of the compound having a radical polymerizable functional group in the photocurable adhesive is 80% by weight or more relative to 100% by weight of the total amount of the photocurable adhesive. The compound having a radical polymerizable functional group includes a compound having an ether bond, and the content of the compound having the ether bond in the photocurable adhesive is 20% by weight or more relative to 100% by weight of the compound having the radical polymerizable functional group. The nonionic photobase generator is a compound represented by the following formula (1), and the content of the nonionic photobase generator in the photocurable adhesive is 0.1% by weight or more and 0.5% by weight or less relative to 100% by weight of the compound having the radical polymerizable functional group.

[0038] [ka]

[0039] The photocurable adhesive of the second invention has the above composition and therefore has an appropriate delayed curing property and a long pot life.

[0040] In this specification, the first and second inventions may be collectively referred to as the present invention.

[0041] In addition, since the photocurable adhesive of the present invention has an appropriate delayed curing property, when bonding adherends together, for example, even when the photocurable adhesive applied to one adherend is irradiated with ultraviolet light and then the photocurable adhesive is attached to the other adherend, the adhesive can still exert its adhesive force. Therefore, the photocurable adhesive of the present invention can bond adherends that are difficult to transmit ultraviolet light to.

[0042] Furthermore, since the photocurable adhesive of the present invention contains a nonionic photobase generator as a photobase generator, it has a long pot life (usable time) and excellent storage stability.

[0043] In the photocurable adhesive of the present invention, in the measurement of the conversion rate described above, the conversion rate of the radical polymerizable functional group immediately after light irradiation is preferably 1% or more, more preferably 5% or more, even more preferably 8% or more, and is preferably 18% or less, more preferably 16% or less, even more preferably 14% or less.

[0044] When the conversion rate of the radical polymerizable functional group immediately after light irradiation is equal to or lower than the upper limit, the delayed curing property of the photocurable adhesive can be adjusted more appropriately, and for example, adherends that are difficult to transmit ultraviolet light can be bonded together more easily. The lower limit of the conversion rate of the radical polymerizable functional group immediately after light irradiation is not particularly limited, but considering the general adhesive properties of the adhesive, it is desirable that it is equal to or higher than the lower limit.

[0045] In the photocurable adhesive of the present invention, the conversion rate of the radical polymerizable functional group when left to stand at 25° C. for 1 hour after light irradiation in the above-mentioned measurement is preferably 85% or more, more preferably 90% or more, and even more preferably 95% or more. The upper limit of the conversion rate of the radical polymerizable functional group when left to stand at 25° C. for 1 hour after light irradiation is not particularly limited, but considering the general adhesive properties as an adhesive, the closer to 100%, the more preferable. The conversion rate of the radical polymerizable functional group when left to stand at 25° C. for 1 hour after light irradiation may be 100% or less, or may be less than 100%.

[0046] When the conversion rate of the radically polymerizable functional group when left to stand at 25°C for 1 hour after light irradiation is within the above range, the delayed curing properties of the photocurable adhesive can be adjusted more appropriately, and the general adhesive properties of the adhesive can be more reliably maintained.

[0047] In the photocurable adhesive of the present invention, the conversion rate of the radically polymerizable functional group immediately after light irradiation or when allowed to stand at 25°C for 1 hour after light irradiation can be adjusted, for example, by the type and content of the compound having a radically polymerizable functional group, the non-ionic photobase generator, and the organic peroxide, as well as the type and content of additives such as acids and bases.

[0048] In addition, in the photocurable adhesive of the present invention, the conversion rate of the radically polymerizable functional group from immediately after light irradiation to when the adhesive is left to stand at 25° C. for 1 hour after light irradiation can be adjusted appropriately depending on the application.

[0049] For example, in the photocurable adhesive of the present invention, in the measurement of the conversion rate described above, when left to stand at 25°C for 1 minute after light irradiation, the conversion rate of the radical polymerizable functional group is preferably 1% or more, more preferably 5% or more, even more preferably 8% or more, and is preferably 20% or less, more preferably 18% or less, even more preferably 16% or less.

[0050] In the photocurable adhesive of the present invention, when left to stand at 25°C for 3 minutes after light irradiation, in the measurement of the conversion rate described above, the conversion rate of the radical polymerizable functional group is preferably 1% or more, more preferably 5% or more, and even more preferably 8% or more, and is preferably 20% or less, more preferably 18% or less, and even more preferably 16% or less.

[0051] In the photocurable adhesive of the present invention, when left to stand at 25°C for 5 minutes after light irradiation, in the measurement of the conversion rate described above, the conversion rate of the radical polymerizable functional group is preferably 1% or more, more preferably 5% or more, and even more preferably 8% or more, and is preferably 20% or less, more preferably 18% or less, and even more preferably 16% or less.

[0052] In the photocurable adhesive of the present invention, when left to stand for 10 minutes at 25°C after light irradiation, in the measurement of the conversion rate described above, the conversion rate of the radical polymerizable functional group is preferably 1% or more, more preferably 5% or more, and even more preferably 8% or more, and is preferably 20% or less, more preferably 18% or less, and even more preferably 16% or less.

[0053] Furthermore, in the photocurable adhesive of the present invention, in the measurement of the conversion rate described above, when left to stand at 25°C for 30 minutes after light irradiation, the conversion rate of the radical polymerizable functional group can be, for example, 20% or more and 80% or less, preferably 25% or more, more preferably 30% or more, and preferably 75% or less, more preferably 70% or less.

[0054] Hereinafter, each material constituting the photocurable adhesive of the present invention will be described in detail.

[0055] (Compound having a radically polymerizable functional group) The photocurable adhesive of the present invention includes a compound having a radically polymerizable functional group. The radically polymerizable functional group is not particularly limited, but is a functional group in which an addition reaction proceeds in a chain reaction manner due to radicals generated by decomposition of a radical generator. Examples of the radically polymerizable functional group include an ethynyl group, an allyl group, a propenyl group, an acetyl group, an acryloyl group, a methacryloyl group, a styryl group, a vinyloxy group, and a vinyl ester group. Among them, from the viewpoint of higher radical polymerizability, the radically polymerizable functional group is preferably a (meth)acryloyl group. At least one radically polymerizable functional group may be contained in one molecule, but it is preferable that a plurality of radically polymerizable functional groups are contained. In this specification, "(meth)acryloyl" refers to "acryloyl" or "methacryloyl".

[0056] In this way, the compound having a radical polymerizable functional group is preferably a compound having a plurality of radical polymerizable functional groups, in which case the cured product of the resin constituted by the compound having the radical polymerizable functional group becomes stronger, and a photocurable adhesive having even stronger adhesive strength can be obtained.

[0057] Examples of compounds having multiple radically polymerizable functional groups include diethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, tetramethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, polytetramethylene glycol di(meth)acrylate, and divinylbenzene. These may be used alone or in combination. In this specification, "(meth)acrylate" refers to "acrylate" or "methacrylate".

[0058] The compound having multiple radical polymerizable functional groups is preferably a monomer having high chain transferability, and particularly preferably has an ether bond. Among them, the compound having multiple radical polymerizable functional groups is preferably diethylene glycol di(meth)acrylate. In this case, the curing of the resin composed of the compound having radical polymerizable functional groups can be further delayed, and the photocurable adhesive having a longer pot life can be obtained.

[0059] Examples of compounds having one radically polymerizable functional group include vinyl monomers containing nitrogen atoms, such as (meth)acryloylmorpholine, N-vinyl-2-pyrrolidone, vinylpyridine, N-vinylcarbazole, (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, isopropyl(meth)acrylamide, hydroxyethyl(meth)acrylamide, and dimethylaminopropylacrylamide. These vinyl monomers may be used alone or in combination. In this specification, "(meth)acryl" refers to "acrylic" or "methacrylic".

[0060] In addition, as a compound having one radically polymerizable functional group, for example, a vinyl monomer containing an oxygen atom such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, (meth)acrylic acid, carboxyethyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, phenoxyethyl (meth)acrylate, ethyl carbitol (meth)acrylate, methoxyethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, (2-methyl-2-ethyl-1,3-dioxolan-4-yl)methyl (meth)acrylate, polyethylene glycol (meth)acrylate, etc. may be used. One of these vinyl monomers may be used alone, or two or more of them may be used in combination.

[0061] The compound having one radical polymerizable functional group is preferably a monomer having high chain transferability, and particularly preferably has an ether bond. Among them, the compound having one radical polymerizable functional group is preferably tetrahydrofurfuryl (meth)acrylate. In this case, the curing of the resin composed of the compound having the radical polymerizable functional group can be further delayed, and the photocurable adhesive having a longer pot life can be obtained.

[0062] The photocurable adhesive of the present invention may contain both a compound having multiple radically polymerizable functional groups and a compound having one radically polymerizable functional group, which can further delay the curing of the resin composed of the compound having the radically polymerizable functional group, while further improving the general adhesive performance as an adhesive.

[0063] In this case, the ratio of the content of the compound having multiple radically polymerizable functional groups to the content of the compound having one radically polymerizable functional group is not particularly limited, but can be, for example, 9:1 to 1:9 by weight, preferably 7:3 to 3:7, and more preferably 6:4 to 4:6.

[0064] The content of the compound having a radical polymerizable functional group is not particularly limited, but is preferably 80% by weight or more, more preferably 90% by weight or more, and preferably 99% by weight or less, more preferably 95% by weight or less, based on 100% by weight of the total amount of the photocurable adhesive. When the content of the compound having a radical polymerizable functional group is within the above range, the curing of the resin composed of the compound having a radical polymerizable functional group can be further delayed, and a photocurable adhesive having a longer pot life can be obtained.

[0065] When the compound having a radical polymerizable functional group includes a compound having an ether bond, the content of the compound having an ether bond in the photocurable adhesive is not particularly limited, but is preferably 20% by weight or more, more preferably 50% by weight or more, even more preferably 80% by weight or more, and is preferably 100% by weight or less, more preferably 95% by weight or less, and even more preferably 90% by weight or less, based on 100% by weight of the compound having a radical polymerizable functional group. When the content of the compound having an ether bond is within the above range, the curing of the resin composed of the compound having a radical polymerizable functional group can be further delayed, and the photocurable adhesive can have a longer pot life. In addition, the compound having an ether bond may be, in addition to tetrahydrofurfuryl (meth)acrylate and diethylene glycol di(meth)acrylate, for example, methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, ethoxyethoxyethyl (meth)acrylate, (2-methyl-2-ethyl-1,3-dioxolan-4-yl)methyl acrylate, cyclic trimethylolpropane formal acrylate, polyethylene glycol (meth)acrylate, etc.

[0066] The photocurable adhesive of the present invention may further contain another vinyl monomer different from the compound having a radically polymerizable functional group, for example, a vinyl monomer that does not contain a nitrogen atom or an oxygen atom in a side chain substituent.

[0067] Examples of other vinyl monomers include (meth)acrylic acid and its esters, such as (meth)acrylic acid, methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. Examples of other vinyl monomers that may be used include vinyl chloride, vinylidene chloride, vinyl acetate, methyl vinyl ether, styrene, and divinylbenzene, as well as compounds having unsaturated double bonds, such as isoprene. These other vinyl monomers may be used alone or in combination.

[0068] (Non-ionic photobase generator) The photocurable adhesive of the present invention contains a non-ionic photobase generator. The non-ionic photobase generator is a substance that generates a base when irradiated with light. Examples of the light include ultraviolet light, visible light, and infrared light.

[0069] The non-ionic photobase generator is not particularly limited, and examples thereof include oxime ester compounds, ammonium compounds, benzoin compounds, dimethoxybenzylurethane compounds, orthonitrobenzylurethane compounds, and coumaric acid amide compounds.

[0070] More specifically, examples of non-ionic photobase generators include 2-(9-oxoxanthen-2-yl)propionic acid 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 9-anthrylmethyl N,N-diethylcarbamate, (E)-1-[3-(2-hydroxyphenyl)-2-propenoyl]piperidine, guanidinium 2-(3-benzoylphenyl)propionate, 1-(anthraquinone-2-yl)ethylimidazole-1-carboxylate, 2-nitrophenylmethyl 4-methacryloyloxypiperidine-1-carboxylate, Examples of such compounds include 1-(anthraquinone-2-yl)-ethyl N,N-dicyclohexylcarbamate, dicyclohexylammonium 2-(3-benzoylphenyl)propionate, cyclohexylammonium 2-(3-benzoylphenyl)propionate, 9-anthrylmethyl N,N-dicyclohexylcarbamate, 1,2-diisopropyl-3-[bis(dimethylamino)methylene]guanidium 2-(3-benzoylphenyl)propionate, or 1,6-hexamethylene-bis(4,5-dimethoxy-2-nitrobenzylcarbamate). These compounds may be used alone or in combination of two or more.

[0071] Among them, the non-ionic photobase generator is preferably a compound (Cou-TMG) represented by the above formula (1). In this case, when the non-ionic photobase generator is irradiated with light to generate a base, it is possible to suppress the simultaneous generation of carbon dioxide, and it is possible to suppress the generation of bubbles in the photocurable adhesive after the adherends are bonded together.

[0072] The content of the nonionic photobase generator is not particularly limited, but is preferably 0.05% by weight or more, more preferably 0.10% by weight or more, and preferably 0.50% by weight or less, more preferably 0.40% by weight or less, based on the total 100% by weight of the compound having a radical polymerizable functional group. When the content of the nonionic photobase generator is within the above range, the curing of the resin composed of the compound having a radical polymerizable functional group can be further delayed, and a photocurable adhesive with a longer pot life can be obtained.

[0073] (organic peroxide) The photocurable adhesive of the present invention contains an organic peroxide. In the present invention, the organic peroxide can be used as a thermal radical generator. The organic peroxide decomposes due to the reducing property of the base component generated from the nonionic photobase generator, generating radicals. The radicals act as the starting point to initiate free radical polymerization of a compound having a radically polymerizable functional group.

[0074] The organic peroxide is not particularly limited, and examples thereof include benzoyl peroxide, diisopropyl peroxycarbonate, dioctyl peroxydicarbonate, t-butyl peroxylaurate, lauroyl peroxide, dioctanoyl peroxide, hydrogen peroxide, acetyl peroxide, cumyl peroxide, t-butyl peroxide, propionyl peroxide, benzoyl peroxide, chlorobenzoyl peroxide, dichlorobenzoyl peroxide, bromomethylbenzoyl peroxide, lauroyl peroxide, ammonium persulfate, and persulfate. Examples of organic peroxides include sodium persulfate, potassium persulfate, diisopropyl peroxycarbonate, tetralin hydroperoxide, 1-phenyl-2-methylpropyl-1-hydroperoxide, t-butyl pertriphenylacetate hydroperoxide, t-butyl performate, t-butyl peracetate, t-butyl perbenzoate, t-butyl perphenylacetate, t-butyl permethoxyacetate, t-butyl per-N-(3-toluyl)carbamate, ammonium bisulfate, sodium bisulfate, and 1,1-di(t-butylperoxy)cyclohexane. These organic peroxides may be used alone or in combination of two or more.

[0075] Among them, the organic peroxide preferably has a percarboxylic acid structure. When the organic peroxide has a percarboxylic acid structure, the redox reaction with the base generated from the non-ionic photobase generator proceeds more efficiently, and radical polymerization can be initiated. The percarboxylic acid structure is a structure having a carbonyl group next to the peroxide structure. In this case, the carbonyl group may be provided adjacent to only one side of the peroxide structure, or may be provided adjacent to both sides of the peroxide structure.

[0076] Examples of organic peroxides having a percarboxylic acid structure include lauroyl peroxide and benzoyl peroxide.

[0077] The content of the organic peroxide is not particularly limited, but is preferably 0.1% by weight or more, more preferably 0.3% by weight or more, and preferably 1.5% by weight or less, more preferably 1.0% by weight or less, based on the total 100% by weight of the compound having a radical polymerizable functional group. When the content of the organic peroxide is equal to or more than the above lower limit, the radical polymerization of the compound having a radical polymerizable functional group proceeds more easily, and polymerization heat is generated, which facilitates the thermal decomposition of the organic peroxide and the subsequent radical polymerization. When the content of the organic peroxide is equal to or less than the above upper limit, the storage stability of the photocurable adhesive can be further improved. When the content of the organic peroxide is within the above range, the curing of the resin composed of the compound having a radical polymerizable functional group can be further delayed.

[0078] (Filler) The photocurable adhesive of the present invention may further contain a filler, which can adjust the adhesive properties of the photocurable adhesive or impart functionality such as electrical conductivity to the photocurable adhesive.

[0079] The filler is not particularly limited, and may be an inorganic filler or an organic filler. Among them, the filler is preferably an inorganic filler. The inorganic filler and the organic filler may be used in combination.

[0080] Examples of the organic filler that can be used include polyethylene fine particles, polypropylene fine particles, polyvinyl alcohol fine particles, polyvinyl butyral fine particles, polyvinyl chloride fine particles, polyvinylidene chloride fine particles, polyvinylidene fluoride fine particles, acrylonitrile fine particles, acrylic rubber fine particles, polystyrene fine particles, divinylbenzene fine particles, polyethylene terephthalate fine particles, polyimide fine particles, polyamide fine particles, cellulose fine particles, etc. These may be used alone or in combination of two or more.

[0081] Examples of inorganic fillers that can be used include metal oxides, metal carbonates, natural minerals, metal hydroxides, carbon materials, metal materials, hollow inorganic fillers, etc. These may be used alone or in combination of two or more.

[0082] Examples of the metal oxide include silica, aluminum oxide, titanium oxide, zirconium oxide, zinc oxide, lead oxide, and indium tin oxide.

[0083] Examples of the metal carbonate include calcium carbonate, magnesium carbonate, and barium carbonate.

[0084] Natural minerals include talc, mica, clay, and the like.

[0085] Examples of the metal hydroxide include aerosil, magnesium hydroxide, and aluminum hydroxide.

[0086] Examples of the carbon material include graphite, carbon black, and carbon nanotubes.

[0087] Examples of the metal material include copper, gold, silver, iron, aluminum, stainless steel, platinum, and palladium.

[0088] Examples of the hollow inorganic filler include glass balloons and shirasu balloons.

[0089] The inorganic filler may be surface-treated with a surface treatment agent such as a silane coupling agent.

[0090] Examples of silane coupling agents include 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropyltrimethoxysilane, 3-aminopropylmethyldimethoxysilane, 3-aminopropyltrimethoxysilane, 3-glycidylpropylmethyldimethoxysilane, 3-glycidylpropyltrimethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-propylisocyanatemethyldimethoxysilane, 3-propylisocyanatetrimethoxysilane, etc. These may be used alone or in combination of two or more.

[0091] The content of the filler is not particularly limited, but is preferably 0.1% by weight or more, more preferably 1% by weight or more, and is preferably 15% by weight or less, more preferably 10% by weight or less, based on 100% by weight of the total of the compounds having radically polymerizable functional groups.

[0092] (Silane coupling agent) The photocurable adhesive of the present invention may further contain a silane coupling agent, which can further improve the adhesive properties of the photocurable adhesive.

[0093] The silane coupling agent is not particularly limited, and for example, epoxy silanes, acrylic silanes, methacrylic silanes, amino silanes, isocyanate silanes, etc. can be used.

[0094] The content of the silane coupling agent is not particularly limited, but is preferably 0.1% by weight or more, more preferably 1% by weight or more, and is preferably 10% by weight or less, more preferably 5% by weight or less, based on 100% by weight of the total of the compounds having radically polymerizable functional groups.

[0095] (solvent) The photocurable adhesive of the present invention may contain a solvent. The solvent is not particularly limited, but may be an organic solvent, water, or the like.

[0096] The organic solvent is not particularly limited, but examples of the organic solvent that can be used include methanol, isopropyl alcohol, n-butanol, benzene, toluene, xylene, ethyl acetate, butyl acetate, acetone, methyl ethyl ketone, methyl isobutyl ketone, tetrahydrofuran, ethylene glycol dimethyl ether, dioxane, acetonitrile, dichloromethane, chloroform, carbon tetrachloride, dimethylformamide, dimethylacetamide, dimethylsulfoxide, and hexamethylphosphoric acid triamide.

[0097] Among them, the organic solvent is preferably a polar solvent. The organic solvent is preferably a solvent having a boiling point of 100° C. or less. Examples of such organic solvents include methanol, isopropyl alcohol, ethyl acetate, acetone, methyl ethyl ketone, tetrahydrofuran, and acetonitrile.

[0098] The content of the solvent is not particularly limited, but considering the general adhesive properties as an adhesive, the smaller the content of the solvent, the more preferable, and the closer to 0% by weight, the more preferable. When the solvent is contained, it is preferably 0.5% by weight or more, more preferably 1% by weight or more, and preferably 10% by weight or less, more preferably 5% by weight or less, and even more preferably 3% by weight or less, based on the total 100% by weight of the compound having a radical polymerizable functional group.

[0099] (Carboxylic Acid) The photocurable adhesive of the present invention may contain a carboxylic acid, in which case the curing of the photocurable adhesive can be further delayed, resulting in an adhesive with a longer pot life.

[0100] The carboxylic acid is not particularly limited, but examples of the carboxylic acid that can be used include formic acid, acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, enanthic acid, caprylic acid, pelargonic acid, capric acid, lauric acid, myristic acid, palmitic acid, margaric acid, stearic acid, oleic acid, linoleic acid, lactic acid, oxalic acid, succinic acid, adipic acid, maleic acid, and benzoic acid.

[0101] The content of the carboxylic acid is not particularly limited, but is preferably 0.005% by weight or more, more preferably 0.01% by weight or more, and is preferably 0.07% by weight or less, more preferably 0.05% by weight or less, based on 100% by weight of the total of the compounds having a radically polymerizable functional group.

[0102] (Other additives) The photocurable adhesive of the present invention may contain other additives as long as they do not impair the object of the present invention.

[0103] Examples of other additives include antioxidants such as phenols, phosphorus, amines, or sulfurs; ultraviolet absorbers such as benzotriazoles or hydroxyphenyltriazines; halogenated flame retardants such as hexabromobiphenyl ether or decabromodiphenyl ether; and flame retardants such as ammonium polyphosphate or trimethyl phosphate. Other additives may include antistatic agents, stabilizers, pigments, dyes, titanium coupling agents, plasticizers, thickeners, viscosity reducers, and thixotropy agents. These additives may be used alone or in combination.

[0104] The content of other additives is not particularly limited, but is preferably 0.1% by weight or more, more preferably 0.3% by weight or more, and is preferably 3% by weight or less, more preferably 1% by weight or less, based on 100% by weight of the total of the compounds having radically polymerizable functional groups.

[0105] The photocurable adhesive of the present invention may contain a photosensitizer. However, from the viewpoint that adhesion is possible even when light of a longer wavelength is used, the content of the photosensitizer is preferably 5% by weight or less, more preferably 4% by weight or less, and even more preferably 3% by weight or less, based on 100% by weight of the compound having a radical polymerizable functional group. However, the photocurable adhesive of the present invention may not contain a photosensitizer, and may contain the photosensitizer in a proportion of 0.01% by weight or more, based on 100% by weight of the compound having a radical polymerizable functional group.

[0106] The photosensitizer is a substance that is excited by irradiation with light and induces decomposition of the thermal radical generator by the photosensitizing effect of the excited photosensitizer. Examples of the light to be irradiated include infrared light, visible light, and ultraviolet light.

[0107] The photosensitizer is not particularly limited, but examples thereof include benzophenone derivatives, thioxanthone derivatives, anthraquinone derivatives, anthracene derivatives, and benzoin derivatives. Among them, the photosensitizer is preferably a benzophenone derivative, a thioxanthone derivative, or an anthraquinone derivative from the viewpoint of being sensitized by light irradiation in the visible light range. Among them, the thioxanthone derivative is more preferable from the viewpoint of being sensitized by light irradiation in the visible light range and being soluble in a compound having a radical polymerizable functional group. The photosensitizer may be used alone or in combination with a plurality of types.

[0108] The photocurable adhesive of the present invention may contain a base multiplier. However, from the viewpoint of being able to cure more quickly, the content of the base multiplier is preferably 5% by weight or less, more preferably 4% by weight or less, and even more preferably 3% by weight or less, based on 100% by weight of the compound having a radical polymerizable functional group. However, the photocurable adhesive of the present invention may not contain a base multiplier, and may contain the base multiplier in a proportion of 0.5% by weight or more, based on 100% by weight of the compound having a radical polymerizable functional group.

[0109] The base amplifier is a substance that uses a base generated from a non-ionic photobase generator as a catalyst to decompose the base and generate a new base. The generated base functions as a new catalyst, autocatalytically generating a large number of bases, and the concentration of the base component increases. The base amplifier may be a low molecular weight compound or a high molecular weight compound. An example of such a base amplifier is 1-(9-fluorenylmethoxycarbonyl)piperidine.

[0110] [Joining method] 1(a) to (c) are diagrams illustrating an example of a bonding method using the photocurable adhesive of the present invention.

[0111] In the bonding method of this embodiment, as shown in Fig. 1(a), first, a photocurable adhesive 1 is applied to a first adherend 2. The photocurable adhesive of the present invention described above can be used as the photocurable adhesive 1. The method for applying the photocurable adhesive 1 is not particularly limited, and examples thereof include a screen printing method and a method of applying the adhesive using a dispenser.

[0112] 1(b), in a state where the photocurable adhesive 1 is applied to the first adherend 2, the photocurable adhesive 1 is irradiated with ultraviolet light A. The irradiation of the ultraviolet light A can be performed, for example, by using an LED lamp whose central wavelength is in the ultraviolet region.

[0113] 1(c), within 10 minutes after irradiation with ultraviolet light A, a second adherend 3 is attached to the photocurable adhesive 1. This allows the first adherend 2 and the second adherend 3 to be bonded together.

[0114] In the bonding method of this embodiment, a photocurable adhesive 1 having an appropriate delayed curing property is used, so that even when the photocurable adhesive 1 is applied only to one of the first adherends 2 and then irradiated with ultraviolet light A, and then the second adherend 3 is bonded to it, it is possible to easily bond the first adherend 2 and the second adherend 3.

[0115] Furthermore, since the photocurable adhesive 1 is irradiated with ultraviolet light A in a step prior to bonding the second adherend 3, it is possible to easily join the first adherend 2 and the second adherend 3 even if the first adherend 2 and the second adherend 3 are adherends that are difficult to transmit ultraviolet light A.

[0116] Examples of the adherends that are difficult to transmit ultraviolet light A include metals or alloys such as iron, aluminum, copper, lead, tin, zinc, nickel, magnesium, titanium, gold, silver, and platinum, or their coated bodies, various plastics or plastic mixtures that are opaque, inorganic materials such as concrete, stone, mortar, ceramic, and porcelain, cellulose-based materials such as wood and paper, and various adherends made of a wide range of materials such as leather. According to the photocurable adhesive of the present invention, even when such adherends are used, it is possible to easily bond the adherends to each other. A primer layer may be applied to the adherends in advance. In this case, the adhesive strength between the adherends can be further increased. Examples of materials for the primer layer include urethane-based primers, polyolefin-based primers, acrylic-based primers, and metal alkoxide-based primers.

[0117] The present invention will now be described in more detail with reference to specific examples and comparative examples, although the present invention is not limited to the following examples.

[0118] In the examples and comparative examples, the following materials were prepared.

[0119] <Compound having a radically polymerizable functional group> A compound having one radically polymerizable functional group; Tetrahydrofurfuryl acrylate (THFA, manufactured by Osaka Organic Chemical Industry Co., Ltd., product number "Viscoat #150")

[0120] A compound having multiple radically polymerizable functional groups; Diethylene glycol diacrylate (DEGDA, manufactured by Tokyo Chemical Industry Co., Ltd.) Tetraethylene glycol diacrylate (TeEGDA, manufactured by Tokyo Chemical Industry Co., Ltd.)

[0121] <Thermal radical generator> organic peroxide; Lauroyl peroxide (LP, NOF Corp., product number "Perloyl L") 1,1-Di(t-butylperoxy)cyclohexane (NOF Corp., product number "Perhexa HC")

[0122] Azo initiators; Azobisisobutyronitrile (AIBN, manufactured by Tokyo Chemical Industry Co., Ltd.)

[0123] <Photobase Generator> Non-ionic photobase generators; The compound of formula (1) above (Cou-TMG) was prepared as follows.

[0124] 10mL of thionyl chloride was added to 2.1g (10mmol) of 2-acetoxycinnamic acid (AcCou-acid) and stirred at room temperature for 12 hours. After that, thionyl chloride was distilled off using a diaphragm pump, and the synthesized chloride was dissolved in 30mL of ultra-dehydrated tetrahydrofuran (THF). 30mL of THF solution containing 2.7g (24mmol, 1.2 equivalents) of TMG (1,1,3,3-tetramethylguanidine) was slowly added dropwise to the THF solution under ice cooling. The resulting mixture was stirred at room temperature for 2 hours, and then quenched by adding water. After the quenched solution, the solvent was distilled off using an evaporator, and 200mL of dichloromethane was added and the mixture was washed twice with a saturated aqueous sodium chloride solution. After that, the washed solution was dried using magnesium sulfate, and the solvent was distilled off using an evaporator to obtain AcCou-TMG (yield 2.8g, yield 91%, yellow viscous liquid).

[0125] 2.4 g (8.0 mmol) of AcCou-TMG was diluted in 30 mL of ultra-dehydrated methanol. 30 mL of saturated aqueous potassium carbonate solution was added to the methanol solution and stirred at room temperature for 3 hours. After that, methanol was removed from the stirred solution using an evaporator, and 100 mL of dichloromethane was added. The resulting solution was separated into an aqueous layer and an oil layer by a liquid separation operation, and then 5 wt% hydrochloric acid was added to the aqueous layer to adjust the pH to 5-6. The solid generated at that time was filtered and dried under reduced pressure to obtain Cou-TMG (yield 1.7 g, yield 80%, total yield 72%, pale yellow solid).

[0126] 1-(anthraquinone-2-yl)ethyl imidazole-1-carboxylate (WPBG-140, Fujifilm Wako Pure Chemical Industries, Ltd., product number "WPBG-140")

[0127] Ionic photobase generators; 2-(9-oxoxanthen-2-yl)propionic acid 1,5,7-triazabicyclo[4.4.0]dec-5-ene (XT-TBD, manufactured by Tokyo Chemical Industry Co., Ltd., product number "XT-TBD")

[0128] <Photoradical generator> Bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (IGM Resins BV, product number "Omnirad819")

[0129] <Carboxylic acid> Lauric acid (LA, manufactured by Tokyo Chemical Industry Co., Ltd.)

[0130] <Filler> Fumed silica (Aerosil 200, manufactured by Nippon Aerosil Co., Ltd.)

[0131] <Silane coupling agent> Trimethoxysilylpropyl acrylate (Shin-Etsu Silicone Co., Ltd., product number "KBM-5103")

[0132] <Solvent> Methanol (MeOH) N,N-Dimethylformamide (DMF)

[0133] (Examples 1 to 12 and Comparative Examples 1 to 6) The materials shown in Tables 1 and 2 below were placed in a brown glass container in the amounts (by weight) shown in Tables 1 and 2 below, and the container was shaken appropriately at room temperature until the solid components were uniformly dissolved, to prepare a photocurable adhesive.

[0134] [evaluation] (Conversion rate) The photocurable adhesives obtained in Examples 1 to 12 and Comparative Examples 1 to 6 were applied to one of the calcium fluoride plates to an area of ​​1 cm × 1 cm and a thickness of 10 μm. Next, in a nitrogen atmosphere, an LED lamp with a central wavelength of 365 nm (manufactured by Iwasaki Electric Co., Ltd., product number "LHPUV365") was used to illuminate the upper surface of the photocurable adhesive with a light intensity of 100 mW / cm. 2 The photocurable adhesive was then sandwiched between the other calcium fluoride plate and the plate.

[0135] Next, the conversion rate of the radical polymerizable functional group immediately after the light irradiation and the conversion rate of the radical polymerizable functional group when the sample was left to stand at 25° C. for 1 hour after the light irradiation were measured. The conversion rate was calculated by measuring the FT-IR spectrum. In Examples 1 to 8 and Comparative Examples 1 to 5, the 850 cm -1 The reference peak is 1615 cm, which is assigned to the C=C of the vinyl group. -1 The FT-IR spectrum was measured using an FT / IR6600 instrument (manufactured by JASCO Corporation) at a measurement wavelength of 4000 cm -1 ~400cm -1 The measurements were performed with 16 scans.

[0136] The conversion rate was calculated according to the following formula (2). Conversion rate (%) = (1 - peak intensity ratio after irradiation / peak intensity ratio before irradiation) × 100 ... Equation (2) Peak intensity ratio before irradiation = (C = C peak intensity before light irradiation / reference peak intensity before light irradiation) Peak intensity ratio after irradiation = (C = C peak intensity after light irradiation / reference peak intensity after light irradiation)

[0137] The conversion rate of the radically polymerizable functional group immediately after the light irradiation was evaluated according to the following evaluation criteria.

[0138] <Evaluation criteria> ○…Conversion rate is 20% or less ×: Conversion rate exceeds 20%

[0139] The conversion rate of the radically polymerizable functional group when the sample was allowed to stand at 25° C. for 1 hour after the light irradiation was evaluated according to the following criteria.

[0140] <Evaluation criteria> ○…Conversion rate is 80% or more ×: Conversion rate is less than 80%

[0141] (Delayed adhesion 1) The photocurable adhesives obtained in Examples 1 to 12 and Comparative Examples 1 to 6 were applied to a glass plate to an area of ​​1 cm × 1 cm and a thickness of 10 μm. Next, after drying at 60° C. for 1 minute, an LED lamp with a central wavelength of 365 nm (manufactured by Iwasaki Electric Co., Ltd., product number "LHPUV365") was used to shine a light of 100 mW / cm from the upper surface side of the photocurable adhesive applied to the glass plate in a nitrogen atmosphere. 2 The sample was irradiated with light for 30 seconds at 3000 mJ / cm 2 ). After that, the other glass plate was attached within 10 seconds, pressed with a weight as a weight, and left to stand at room temperature for 60 minutes to obtain an evaluation sample. Next, the maximum stress was measured when pulled in the shear direction at a speed of 10 mm / min using a tensile tester (manufactured by Imada Seisakusho, product number "Tension and Compression Tester SVZ-50NB") in an atmosphere of 25°C. The delayed adhesion (delayed curing) was evaluated according to the following evaluation criteria.

[0142] (Delayed adhesion 2) The photocurable adhesives obtained in Examples 1 to 12 and Comparative Examples 1 to 6 were applied to a copper plate to an area of ​​1 cm × 1 cm and a thickness of 10 μm. Next, after drying at 60°C for 1 minute, an LED lamp with a central wavelength of 365 nm (manufactured by Iwasaki Electric Co., Ltd., product number "LHPUV365") was used to shine a light of 100 mW / cm from the upper surface side of the photocurable adhesive applied to the copper plate in a nitrogen atmosphere. 2 The sample was irradiated with light for 30 seconds at 3000 mJ / cm 2). After that, the other copper plate was attached within 10 seconds, pressed with a weight as a weight, and left to stand at room temperature for 60 minutes to obtain an evaluation sample. Next, the maximum stress was measured when pulled in the shear direction at a speed of 10 mm / min using a tensile tester (manufactured by Imada Seisakusho, product number "Tension and Compression Tester SVZ-50NB") in an atmosphere of 25°C. The delayed adhesion (delayed curing) was evaluated according to the following evaluation criteria.

[0143] (Delayed adhesion 3) A copper plate was coated with trimethoxysilylpropyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd.) using a brush, and heated at 100°C for 30 minutes to obtain a copper plate on which a primer layer was formed. The photocurable adhesives obtained in Examples 1 to 12 and Comparative Examples 1 to 6 were coated on the copper plate on which the primer layer was formed to an area of ​​1 cm × 1 cm and a thickness of 10 μm. Next, after drying at 60°C for 1 minute, an LED lamp with a central wavelength of 365 nm (manufactured by Iwasaki Electric Co., Ltd., product number "LHPUV365") was used to illuminate the upper surface of the photocurable adhesive coated on the copper plate on which the primer layer was formed, with a light intensity of 100 mW / cm. 2 The sample was irradiated with light for 30 seconds at 3000 mJ / cm 2 ). After that, the copper plate on which the other primer layer was formed was attached within 10 seconds, pressed with a weight as a weight, and left to stand at room temperature for 60 minutes to obtain an evaluation sample. Next, the maximum stress was measured when pulled in the shear direction at a speed of 10 mm / min using a tensile tester (manufactured by Imada Manufacturing Co., Ltd., product number "Tension and Compression Tester SVZ-50NB") in an atmosphere of 25°C. The delayed adhesion (delayed curing) was evaluated according to the following evaluation criteria.

[0144] <Evaluation criteria for delayed adhesion 1 to 3> A: Maximum stress is 0.30MPa or more B: Maximum stress is 0.01MPa or more and less than 0.30MPa C: Maximum stress is less than 0.01MPa

[0145] (Storage stability) The photocurable adhesives obtained in Examples 1 to 12 and Comparative Examples 1 to 6 were stored in vials at room temperature for 3 months, and then an evaluation was performed to see whether they could be applied to a glass plate with an area of ​​1 cm × 1 cm and a thickness of 10 μm.

[0146] The storage stability was evaluated according to the following criteria.

[0147] <Evaluation criteria> 〇…Can be applied even after 3 months ×…Hardens within 3 months and becomes impossible to apply

[0148] (Foaming) The photocurable adhesives obtained in Examples 1 to 12 and Comparative Examples 1, 3 to 6 were applied to a glass plate to an area of ​​1 cm × 1 cm and a thickness of 10 μm. Next, after drying at 60°C for 1 minute, an LED lamp with a central wavelength of 365 nm (manufactured by Iwasaki Electric Co., Ltd., product number "LHPUV365") was used to shine a light of 100 mW / cm from the upper surface side of the photocurable adhesive applied to the glass plate in a nitrogen atmosphere. 2 The sample was irradiated with light for 30 seconds at 3000 mJ / cm 2 ). After that, the other glass plate was attached within 10 seconds, pressure-bonded using a weight as a weight, and left to stand at room temperature for 60 minutes to obtain a sample for evaluation. After that, the sample for evaluation was visually observed. The foaming property was evaluated according to the following evaluation criteria.

[0149] <Evaluation criteria> 〇…No foaming at all △: Foaming is present

[0150] The compositions of the photocurable adhesives and the results are shown in Tables 1 and 2 below.

[0151] [Table 1]

[0152] [Table 2] [Explanation of symbols]

[0153] 1...Light-curing adhesive 2...First adherend 3...Second adherend A...Ultraviolet light

Claims

1. A photocurable adhesive comprising a compound having a radically polymerizable functional group, a non-ionic photobase generator, and an organic peroxide, The photocurable adhesive was applied to one of the calcium fluoride plates to an area of ​​1 cm × 1 cm and a thickness of 10 μm, and in a nitrogen atmosphere, an LED lamp with a central wavelength of 365 nm was used to irradiate the photocurable adhesive from the upper surface side of the calcium fluoride plate with a light intensity of 100 mW / cm. 2 and then sandwiched between another calcium fluoride plate, the photocurable adhesive has a conversion rate of 20% or less of the radical polymerizable functional group immediately after the light irradiation, and a conversion rate of 80% or more when allowed to stand at 25°C for 1 hour after the light irradiation.

2. A photocurable adhesive comprising a compound having a radically polymerizable functional group, a non-ionic photobase generator, and an organic peroxide, the content of the compound having a radical polymerizable functional group in the photocurable adhesive is 80% by weight or more relative to 100% by weight of the total amount of the photocurable adhesive; the compound having a radical polymerizable functional group includes a compound having an ether bond, the content of the compound having an ether bond in the photocurable adhesive is 20% by weight or more relative to 100% by weight of the compound having a radical polymerizable functional group; The nonionic photobase generator is a compound represented by the following formula (1): A photocurable adhesive, wherein the content of the nonionic photobase generator in the photocurable adhesive is 0.1% by weight or more and 0.5% by weight or less, based on 100% by weight of the compound having a radical polymerizable functional group. 【Chemistry 1】

3. The photocurable adhesive according to claim 1 , wherein the compound having a radically polymerizable functional group has an ether bond.

4. The photocurable adhesive according to claim 1 , wherein the compound having a radically polymerizable functional group has a plurality of radically polymerizable functional groups.

5. The photocurable adhesive according to claim 1 , wherein the nonionic photobase generator is a compound represented by the following formula (1): 【Chemistry 2】

6. The photocurable adhesive according to claim 1 , wherein the organic peroxide has a percarboxylic acid structure.

7. The photocurable adhesive according to claim 1 or 2, further comprising a silane coupling agent.

8. 8. The photocurable adhesive according to claim 7, wherein the content of the silane coupling agent in the photocurable adhesive is 0.1% by weight or more and 10% by weight or less relative to 100% by weight of the compound having a radical polymerizable functional group.

9. The photocurable adhesive according to claim 1 or 2, further comprising a filler.

10. 3. The photocurable adhesive according to claim 1, wherein the content of the solvent in the photocurable adhesive is 10% by weight or less relative to 100% by weight of the compound having a radical polymerizable functional group.

11. A method for bonding adherends together using the photocurable adhesive according to claim 1 or 2, comprising the steps of: a step of applying the photocurable adhesive to one of the adherends with ultraviolet light; a step of attaching another adherend to the photocurable adhesive within 10 minutes after the irradiation of the ultraviolet light; The joining method comprises:

12. The bonding method according to claim 11 , further comprising the step of applying a primer layer to at least one of the first and second adherends in advance.

Citation Information

Patent Citations

  • Photocurable adhesive composition

    JP2023011929A